Life Table and Population Parameters of Nilaparvata lugens Stal. (Homoptera: Delphacidae) on Rice - San San Win; Rita Muhamad; Zainal Abidin Mior Ahmad; Nur Azura Adam (Tropical Life Sciences Research, 2011)
Survival and fertility characteristics of the brown planthopper (BPH), Nilaparvata lugens were assessed in the laboratory and field. Life tables and population parameters of the BPH were constructed in an environment with unlimited food supply and that was free of natural enemies. The highest mortality occurred in the immature stage, especially in the first and second instars. The life table analysis showed that the population density of BPH decreased gradually. The survival ratio of male to female was 0.512:0.488. The females lived for a maximum of 20 days. The trend of oviposition showed a peak at around the tenth day of the female life. The highest number of eggs produced per female per day was 9.63. The intrinsic rate of increase (rm) in egg production per female per day was 0.0677 and the daily finite of increase (?) was 1.0688 females per female per day, with a mean generation time (T) of 34.05 days. The net reproductive rate (Ro) of the population was 10.02. The population doubling time (DT) was 10.42 days. Kadar kemandirian dan fertility benah perang (BPH), Nilaparvata lugens telah dibuat di makmal dan di ladang. Jadual hidup dan parameter populasi benah perang dibuat berdasarkan pada keadaan makanan tak terbatas dan bebas dari musuh semula jadi. Mortaliti tertinggi didapati pada peringkat muda, terutama pada peringkat nimfa satu dan dua. Analisis jadual hidup ini menunjukkan densiti populasi N. lugens berkurang pada kadar yang perlahan. Nisbah jantina jantan dan betina ialah 0.512:0.488. Betina dewasa dapat hidup maksimum 20 hari. Corak oviposisi dengan pemuncak didapati pada akhir kehidupan betina. Purata telur tertinggi yang dihasikan per betina dewasa per hari ialah 9.63. Kadar pertambahan intrinsik semula jadi (rm) ialah 0.0677 per betina per hari dan kadar pertambahan finit harian (?) ialah 1.0688 betina per betina per hari, dengan purata waktu generasi (T) ialah 34.05 hari. Kadar pembiakan net (Ro) untuk populasi bersangkutan ialah 10.02. Waktu penggandaan populasi (DT) ialah 10.42 hari.